To use Hess's law, we need to manipulate the given equations so that they can be combined to form the target equation: C s + 2H2 g --> CH4 g . First, we need to reverse equation 2 to get H2 g and O2 g on the reactant side: 2' 2H2 g + O2 g --> 2H2O l H' = -472 kJ/molNow, we need to form CH4 g in the products. We can do this by adding the following equation: 4 C s + 2H2O l --> CH4 g + O2 g H = x kJ/molWe can obtain equation 4 by combining equations 1 , 2' , and 3 . Let's do that: 1 + 2' + 3 = 4 2H2 g + O2 g --> 2H2O l H = -572 kJ/mol2H2 g + O2 g --> 2H2O l H' = -472 kJ/molC s + O2 g --> CO2 g H = -394 kJ/mol-----------------------------------------C s + 2H2O l + 2H2 g + O2 g --> 2H2O l + CO2 g + CH4 g + O2 g Simplifying the equation, we get:C s + 2H2 g --> CH4 g + CO2 g Now, we need to subtract equation 3 from the combined equation to get the target equation: 4 - 3 = Target EquationC s + 2H2 g --> CH4 g + CO2 g H = x kJ/mol- C s + O2 g --> CO2 g H = -394 kJ/mol -----------------------------------------C s + 2H2 g --> CH4 g H = x + 394 kJ/molNow, we can find the enthalpy change for the target equation by adding the enthalpy changes of the combined equations:H = H + H' + HH = -572 kJ/mol + -472 kJ/mol + -394 kJ/mol H = -1438 kJ/molSo, the enthalpy change for the target equation is:H = x + 394 kJ/molx = -1438 kJ/mol - 394 kJ/molx = -1832 kJ/molTherefore, the enthalpy change for the reaction C s + 2H2 g --> CH4 g is -1832 kJ/mol.